2018
DOI: 10.1097/coc.0000000000000230
|View full text |Cite
|
Sign up to set email alerts
|

Brain Metastases at Presentation in Patients With Non–Small Cell Lung Cancer

Abstract: Brain radiotherapy is indicated in over 8% of patients with NSCLC at presentation. We demonstrated that the risk of brain metastasis at presentation may be stratified with the use of 6 clinical factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
15
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 15 publications
4
15
1
4
Order By: Relevance
“…Morgensztern et al found better survival rates of AD compared to SQCC in stage IV lung cancer patients [ 9 ]. Waqar et al suggested that brain irradiation is 67% more likely to be used in AD compared to SQCC [ 10 ]. Eberhardt et al reported that single metastatic lesions in the adrenals showed significantly poor prognosis, which could not be confirmed in all patient groups analyzed [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Morgensztern et al found better survival rates of AD compared to SQCC in stage IV lung cancer patients [ 9 ]. Waqar et al suggested that brain irradiation is 67% more likely to be used in AD compared to SQCC [ 10 ]. Eberhardt et al reported that single metastatic lesions in the adrenals showed significantly poor prognosis, which could not be confirmed in all patient groups analyzed [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…По данным литературы, прогностическую значимость процессов метастазирования РЛ имеют уровни в крови TGF-β 1 [9], VEGF и ОР [12], FN [13,19], CRP [10,20] и α 2 MG [14]. По результатам наших исследований, у больных основной группы с МГМ (табл.…”
Section: результаты и обсуждениеunclassified
“…При этом рассматривают дуральные, лептоменингеальные, внутрисосудистые и милиарные локализации МГМ [19]. В контексте сказанного в настоящее время у больных РЛ иногда выполняют облучение головы с целью профилактики возможного метастазирования опухоли в мозг [20].…”
unclassified
“…Brain metastasis (BM) has long been recognized to represent a common event in NSCLC. About 10%-25% of NSCLC patients present with BM upon the initial diagnosis, and up to 50% will develop BM at some point during the course of the disease [3,4] . The incidence of BM appears to have increased in the past decade due to the wide use of magnetic resonance imaging to detect smaller lesions as well as to the evolution of more effective systemic therapy leading to better control of extra-cranial disease and prolonged survival [5,6] .…”
Section: Introductionmentioning
confidence: 99%